Fenomen „młodych pisarzy” w literaturze włoskiej końca XX wieku - Kornacka, Barbara (Wydawnictwo Naukowe UAM, 2016)
The book entitled the “Phenomenon of young writers in Italian literature of the 20th century” discusses a contentious issue in Italian literature. The definition of this trend draws on three meanings of the word young; related to chronological age, professional experience and subject matter. The 1980s generation of young writers emerged as a response to the literary stagnation of the previous decade and in the context of postmodernism. Publishing houses played an important role through promoting young literary debuts in the first half of the decade (Tondelli, De Carlo, Del Giudice, Busi), and later the rich prose of young writers of the late-1980s. Pier Vittorio Tondelli was of great importance for the young writers of the 1990s, as were the regular meetings of literary circles in Reggio Emilia. The young prose of the 1990s can be characterised by the thematization of youth, multimedia contaminations and motifs derived from the pulp genre. Also visible are other peripheral trends, which extend beyond the time frame of the 20th century.

Starzejący się wiek XX, paradoksalnie, zbiega się z kolejną nawracającą falą „retoryki młodości”, czego wyrazem w literaturze włoskiej jest m.in. fenomen „młodych pisarzy”, usankcjonowany ostatecznie na Targach Książki we Frankfurcie w roku 1985. Zjawisko to, będące po części produktem strategii marketingowych przemysłu wydawniczego, wpisuje się w ważną cezurę w historii literatury włoskiej, wynikającą z wymiany pokoleniowej, jaka ma wówczas miejsce, oraz z głębszych zmian natury czysto literackiej, związanych także z nowym postmodernistycznym paradygmatem. „Młodzi pisarze” końca XX wieku – wbrew upraszczającym założeniom tej formuły – okazują się być jednak dość pojemnym i wieloznacznym pojęciem, mieszczącym w sobie niejednorodne tendencje stylistyczne i tematyczne. Niniejsza pozycja stawia sobie za cel systematyczny opis – na ile pozwala nań niewielki dystans czasowy – oraz przybliżenie polskiemu czytelnikowi zjawiska i literatury „młodych pisarzy”, stanowiącej znaczący fragment najnowszej historii literatury włoskiej.
The phenomenon of 'young writers' in late-20th century Italian literature
Keywords: młodzi pisarze; literatura włoska lat 80 i 90 XX wieku